Roman Ingarden's Analysis of the Poem "Nietzsche adan Perempuan Berhati Pos Ronda" by Beni Satryo - Titasari, Dewi Fitri (INDONESIAN JOURNAL OF SUSTAINABILITY, 2024)
The development of poetry in the contemporary era shows an increasingly rapid creative value, especially through the contribution of young poets who actively utilize social media as a platform to display their literary works. This phenomenon not only creates diversity in the genre of poetry, but also presents a unique perspective on social reality. This research aims to describe the structure of poetry in Beni Satryo's poem entitled "Nietzsche and the Woman with the Heart of Pos Ronda" according to Roman Ingarden's normative strata. This research uses a qualitative descriptive approach, collecting data using the literature study method with the technique of simak catat. The data is studied with an objective approach and presented descriptively. The results show that the poem "Nietzsche and the Woman with the Heart of the Ronda Post" describes the sadness and twists and turns of a widow's life, reflecting the views of a society that undervalues the role of women in social life.